Influence of relative humidity on HEPA filters during and after loading with soot particles. Issue 7 (2nd July 2020) - Godoy, Charlotte; Thomas, Dominique
Abstract: One of the most frequently used methods to purify air contaminated by particles, in many industrial processes, is filter media. Although the performance of filter media is relatively well documented under standard conditions (humidity and ambient temperature), few studies are interested in the interaction between moisture and the deposition of particles collected. The proposed study aims to establish the performance of a fibrous media with aerosols composed of nanostructured solid particles (soot) and the influence of relative humidity (RH) on its pressure drop. In a first part, the impact of relative humidity on the mass loading capacity of flat HEPA filter with soot particles during clogging is investigated. In a second part, exposure of filters loaded (at 35% RH) with soot particles by a clean air at relative humidity rate between 50 and 90% is tested. The results show a significant decrease of pressure drop for high relative humidity rate. Knowing soot particles are non-hygroscopic and non-hydrophilic, shows an interesting phenomenon, which could be not link to the nature of the particles. A model has be done with the results obtained. Copyright © 2020 American Association for Aerosol Research